2011
DOI: 10.1182/blood-2011-04-346437
|View full text |Cite
|
Sign up to set email alerts
|

Early death rate in acute promyelocytic leukemia remains high despite all-trans retinoic acid

Abstract: The incidence of early death in a large population of unselected patients with acute promyelocytic leukemia (APL) remains unknown because of the paucity of outcome data available for patients treated outside of clinical trials. We undertook an epidemiologic study to estimate the true rate of early death with data from the Surveillance, Epidemiology, and End Results (SEER) program. A total of 1400 patients with a diagnosis of APL between 1992 and 2007 were identified. The overall early death rate was 17.3%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
258
5
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(281 citation statements)
references
References 35 publications
15
258
5
3
Order By: Relevance
“…Conventional treatment (anthracycline 1 ATRA) for APL is usually reported to cure >80% of patients, although, because of early death, this may occur in only 60-70% of patients in community settings [28]. To dispense with chemotherapy MD Anderson investigators administered, in a single-arm trial, only ATO1ATRA to patients presenting with WBC < 10,000 [29].…”
Section: Treatmentmentioning
confidence: 99%
“…Conventional treatment (anthracycline 1 ATRA) for APL is usually reported to cure >80% of patients, although, because of early death, this may occur in only 60-70% of patients in community settings [28]. To dispense with chemotherapy MD Anderson investigators administered, in a single-arm trial, only ATO1ATRA to patients presenting with WBC < 10,000 [29].…”
Section: Treatmentmentioning
confidence: 99%
“…ED, the term proposed 20 years ago when ATRA had not been widely used, 94 has recently attracted attention again from investigators. 33,95,96 Park et al 97 reported 1400 cases of APL from 1992 to 2007, the overall ED rate was 17.3%, and only a modest change in ED was observed over time. Lehmann et al 98 reported 105 cases of APL patients among whom the frequency of ED (within 30 days) actually reached 29%, a rate significantly higher than those in non-APL AML, especially evident in the elderly (460 years) population.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Our aim is to deliver the most timely and best treatment to each newly diagnosed APL patient, that is, to mobilize our entire human and material resources if necessary, including emergency room, intensive care unit, multi-disciplinary team of physicians and nurses, to ensure the maximum saving of lives at the onset of disease. More importantly, as Park et al 97 mentioned, there is a clear need to provide the knowledge necessary to recognize APL as a medical emergency that requires specific and simultaneous actions, including a prompt initiation of ATRA, aggressive supportive care to counteract the coagulopathy and transfer to experienced medical centers when the disease is first suspected.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A second problem are early deaths in APL. The early death rate in population-based studies [12] is always higher than early death rate in patients enrolled on clinical trials. Investigators from France looked at all patients from a specific geographic area who developed APL to try to determine if rapid institution of ATRA, which ameliorates the associated coagulopathy, would be effective in reducing the early mortality rate.…”
Section: Richard M Stonementioning
confidence: 99%